2020
DOI: 10.1186/s13104-020-05053-x
|View full text |Cite
|
Sign up to set email alerts
|

The cholesterol 24-hydroxylase activates autophagy and decreases mutant huntingtin build-up in a neuroblastoma culture model of Huntington’s disease

Abstract: Objective: Compromised brain cholesterol turnover and altered regulation of brain cholesterol metabolism have been allied with some neurodegenerative diseases, including Huntington's disease (HD). Following our previous studies in HD, in this study we aim to investigate in vitro in a neuroblastoma cellular model of HD, the effect of CYP46A1 overexpression, an essential enzyme in cholesterol metabolism, on huntingtin aggregation and levels. Results: We found that CYP46A1 reduces the quantity and size of mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…72 Overexpression of cytochrome P450 family 46 subfamily a member 1 (CYP46A1), a cardinal enzyme in brain cholesterol metabolism, attenuated the size and quantity of mHTT aggregates in a neuroblastoma cell HD model which was linked to mild autophagy induction. 73 Huntingtin (HTT) plays various roles in mitophagy, selective autophagy of mitochondria, such as promoting mitophagy initiation and the recruitment of mitophagy receptors.…”
Section: Adap Tive Autophagy In Hdmentioning
confidence: 99%
“…72 Overexpression of cytochrome P450 family 46 subfamily a member 1 (CYP46A1), a cardinal enzyme in brain cholesterol metabolism, attenuated the size and quantity of mHTT aggregates in a neuroblastoma cell HD model which was linked to mild autophagy induction. 73 Huntingtin (HTT) plays various roles in mitophagy, selective autophagy of mitochondria, such as promoting mitophagy initiation and the recruitment of mitophagy receptors.…”
Section: Adap Tive Autophagy In Hdmentioning
confidence: 99%
“…The 24OHC-liked compound reversed schizophrenia-liked behavioral in animal models provides strong evidence for this hypothesis ( 22 ). On the other hand, previous studies have been indicated that 24OHC may facilitate inflammation, oxidative stress, autophagy, and necroptosis, which are also main driving forces in schizophrenia ( 51 53 ). These data implied that lowering 24OHC levels might be a therapeutic way in schizophrenia treatment.…”
Section: Discussionmentioning
confidence: 93%
“…Other studies support the role of CYP46A1 overexpression in alleviating HD phenotypes. Indeed, in a neuroblastoma culture model of HD, CYP46A1 over-expression reduces the quantity and size of mHTT aggregates, as well as the levels of mHTT protein, potentially through the activation of autophagy ( Nóbrega et al, 2020 ). Interestingly, CYP46A1 overexpression protects against NMDA-mediated excitotoxicity in a cellular model of HD ( Boussicault et al, 2018 ).…”
Section: Clinical Strategies To Manipulate Cholesterol Metabolism In ...mentioning
confidence: 99%